The inner temperature of the olives (cv. Leccino) before processing affects the volatile profile and the composition of the oil. (March 2020) - Dourou, Athanasia-Maria; Brizzolara, Stefano; Meoni, Gaia; Tenori, Leonardo; Famiani, Franco; Luchinat, Claudio; Tonutti, Pietro
Graphical abstract: Highlights: Pre-processing temperature of olives affects the volatile profiles of the oil. Lowering fruit temperature enhances green traits of the oil. Reduction of off-flavours compounds in oils from fruit cooled at 10 and 15 °C. More pronounced effects of lowering fruit temperature in oils obtained from ripe fruit. Abstract: The effects of pre-processing decreasing temperature (19, 15 and 10 °C) of olive fruit (cv. Leccino) harvested at three developmental stages (semi-ripe, ripe, advanced ripening) have been evaluated on oil in terms of basic quality parameters, composition, organoleptic traits, and aroma profiles. A total of 40 metabolites (volatiles and non-volatiles) were identified by 1 H NMR and GC/MS analyses. Multivariate statistical analysis showed that samples obtained from ripe and advanced ripe olives cooled at 10 and 15 °C better correlated with C6 aldehydes, mainly associated with herbal/green olfactory traits. Compounds responsible for sweet/fruity traits were more abundantly present in oil extracted from 19 °C olive samples. Decreasing pulp temperature before crushing also resulted in reduced presence of 1-penten-3-ol, 1-penten-3-one, acetic acid and ethyl alcohol, associated with specific defects of the oil. Results indicate that slightly lowering fruit temperature just before crushing modulates oil composition by reducing oil off flavours while enhancing green and fresh attributes in particular when ripe olives are processed.